Amphiphilic copolymers reduce aggregation of unfolded lysozyme more effectively than polyethylene glycol. (8th February 2017) - Chin, Jaemin; Mustafi, Devkumar; Poellmann, Michael J; Lee, Raphael C
Abstract: Certain amphiphilic block copolymers are known to prevent aggregation of unfolded proteins. To better understand the mechanism of this effect, the optical properties of heat-denatured and dithiothreitol reduced lysozyme were evaluated with respect to controls using UV–Vis spectroscopy, transmission electron microscopy (TEM) and circular dichroism (CD) measurements. Then, the effects of adding Polyethylene Glycol (8000 Da), the triblock surfactant Poloxamer 188 (P188), and the tetrablock copolymer Tetronic 1107 (T1107) to the lysozyme solution were compared. Overall, T1107 was found to be more effective than P188 in inhibiting aggregation, while PEG exhibited no efficacy. TEM imaging of heat-denatured and reduced lysozymes revealed spherical aggregates with on average 250–450 nm diameter. Using CD, more soluble lysozyme was recovered with T1107 than P188 with β -sheet secondary structure. The greater effectiveness of the larger T1107 in preventing aggregation of unfolded lysozyme than the smaller P188 and PEG points to steric hindrance at play; signifying the importance of size match between the hydrophobic region of denatured protein and that of amphiphilic copolymers. Thus, our results corroborate that certain multi-block copolymers are effective in preventing heat-induced aggregation of reduced lysozymes and future studies warrant more detailed focus on specific applications of these copolymers.